Patterns and Attitudes toward Smokeless Tobacco Consumption among Women in a Rural Setting (Central Medical College Journal, 2025)
Background: Smokeless tobacco (SLT) consumption is culturally practiced in Bangladesh. Despite its popularity, inadequate information is available on SLT usage. The common belief among the consumers of smokeless tobacco is that is not as hazardous as smoking tobacco. Objective: To assess the patterns and attitudes toward smokeless tobacco consumption among women in a rural setting. Methods: The cross-sectional study is conducted over ten days among 288 women in Sreemantapur rural area at Sadar South Upazilla under Cumilla district. Respondents are choosed by convenience sampling technique; data collection method is face-to-face interview with a semi-structured questionnaire. Results: Out of 288 respondents, the majority (37.5%) of the participant’s age is